The Relation of Acid Fast Bacilli with Ziehl Neelsen Staining and Histopathologic Examination of Biopsy Specimens in Extrapulmonary TB Suspected Patients - Yani Triyani; Maya Tejasari; Wida Purbaningsih; Sadeli Masria; Titik Respati (Universitas Islam Bandung, 2020)
Case finding and diagnosis of extrapulmonary tuberculosis (EPTB) infection are difficult to enforce in the field because not all primary services can do it. The 2016 TB Health Guidelines, the diagnosis of EPTB, is made by clinical, bacteriological, and or histopathological examination from the biopsy. This study analyzed tissue biopsy histopathologically and bacterial of acid-fast bacilli (AFB) slide stained (by Ziehl Neelsen method) associated with histopathological features in patients diagnosed with EPTB. The study conducted in the laboratory of Al Islam Hospital Bandung from November to December 2017. Histopathological diagnosis collected from 1,304 patients, with 760 noninfectious disease patients (58%), 461 infectious disease patients (35%), and 83 (7%) infectious and non-infectious patients. EPTB found in 10% of infectious disease patients. EPTB was mostly originating in neck lymph nodes (18 of 37 patients). The histopathological diagnosis of EPTB infection found that 36 of 37 patients showed granulomas (+), but AFB stained (+) found only in 6 of 37 slides. It is possible because of granulomas is a collection of several inflammatory cells. The lesions develop granulomatous defined by necrosis. There are fewer organisms that usually exist on the periphery both inside and outside the site of infection. This important immune reaction provides the body with protection from antigen recognition, very important in the case of mycobacterial infections. In conclusion, there is no relation between AFB and histopathological examination in patients with EPTB. HUBUNGAN ANTARA BASIL TAHAN ASAM PEWARNAAN ZIEHL NEELSEN DAN HASIL PEMERIKSAAN HISTOPATOLOGI PADA PREPARAT JARINGAN BIOPSI PASIEN TUBERKULOSIS EKSTRAPARUPenemuan kasus dan diagnosis infeksi tuberkulosis ekstraparu (TBEP) sulit ditegakkan di lapangan karena tidak semua layanan primer dapat melakukannya. Berdasar atas Pedoman Kesehatan TB 2016 untuk Pengendalian TB, diagnosis TBEP dapat dilakukan dengan pemeriksaan klinis, bakteriologis, dan atau histopatologis dari biopsi. Penelitian ini menganalisis semua sediaan histopatologis dari biopsi jaringan dan menganalisis pemeriksaan bakteriologis pewarnaan basil tahan asam (BTA) (dengan metode Ziehl Neelsen) terkait dengan gambaran histopatologis pada pasien yang didiagnosis TBEP. Penelitian dilaksanakan di Laboratorium RS Al Islam Bandung dari November hingga Desember 2017. Diperoleh 1.304 pasien dengan sediaan histopatologis, diagnosis penyakit noninfeksi 760 pasien (58%), penyakit infeksi 461 pasien (35%), penyakit gabungan (infeksi dan noninfeksi) 83 pasien (7%), serta TBEP 10% dari seluruh penyakit infeksi. Sebagian besar TBEP berasal dari kelenjar getah bening leher (18 dari 37 pasien). Hasil diagnosis infeksi TBEP 36 dari 37 pasien ditemukan gambaran histopatologisnya dengan granuloma (+), tetapi dengan pewarnaan BTA (+) hanya 6 dari 37 sediaan. Hal ini mungkin karena granuloma adalah kumpulan beberapa sel inflamasi yang berkembang menjadi nekrosis sehingga lebih sedikit organisme yang biasanya terdapat di dalam maupun di luar lesi. Pembentukan granuloma merupakan reaksi kekebalan yang memberi perlindungan tubuh dari serangan antigen dalam kasus infeksi mikobakterium. Simpulan, tidak terdapat hubungan hasil pewarnaan BTA dengan pemeriksaan histopatologis pada pasien TBEP.